Cardiovascular diseases («Internal Medicine». Modul 2). Topics for self-education of students: Part 1 - Berezin, O. E.; Vizir, V. A.; Demidenko, O. V.; Березін, Олександр Євгенійович; Візір, Вадим Анатолійович; Деміденко, Олександр Вікторович (Запорізький державний медичний університет, 2019)
The executive task force is provided to the students of 5th courses of medical faculties for self-education on some topics in the fields of cardiovascular diseases incorporated into the discipline «Internal Medicine». There is the information about the most important topics regarding diagnosis of cardiac diseases.
Захворювання серцево-судинної системи. Питання для самостійної роботи студентів («Внутрішня медицина». Модуль 2). Ч. 1